Effect of Intellectual Property Rights Protection on Services Export Diversification - Sèna Kimm Gnangnon (ZBW - Leibniz Information Centre for Economics, 2022)
The effect of the betterment of enforced intellectual property rights (IPRs) provisions on services export concentration has been investigated. The analysis has used a panel dataset of 103 countries (both developed and developing countries) over the period of 1985-2014. It has revealed that countries with low levels of enforced IPRs tend to concentrate their services exports on few items, while countries with a high degree of enforced IPRs experience a greater level of services export diversification. Furthermore, the betterment of IPRs protection influences positively services export diversification, and the magnitude of this positive effect is higher for advanced countries compared to relatively less advanced economies. These results are particularly relevant for developing countries, including the least-developed countries that have both weakly enforced IPRs and high levels of services export concentration.
Keywords: E31; F13; O34; 330; Intellectual property rights; Services export concentration